2019
DOI: 10.2196/12501
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Culturally Tailored Website to Increase Fruit and Vegetable Intake and Physical Activity Levels in African American Mother-Child Dyads: Observational Study

Abstract: Background African American youth (aged 8-14 years) do not adhere to national dietary and physical activity guidelines. Nonadherence to these recommendations contributes to disproportionate rates of obesity compared with their white counterparts. Culturally tailored electronic health (eHealth) solutions are needed to communicate nutrition and physical activity messages that resonate with this target population. Objective This study aimed to identify the impact of exposu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Racial and ethnic minority youth are heavily targeted for fast food marketing [49,50], and communities of color tend to be inundated by food swamps (ie, an abundance of fast food restaurants concentrated in a ZIP Code). Therefore, in order to act against these high-calorie, nutrient-poor advertising messages [51], culturally tailored approaches are needed to promote healthful eating behaviors among this population [52]. In addition, health literacy has been identified as a key social determinant of health among adolescents [53].…”
Section: Future Directionsmentioning
confidence: 99%
“…Racial and ethnic minority youth are heavily targeted for fast food marketing [49,50], and communities of color tend to be inundated by food swamps (ie, an abundance of fast food restaurants concentrated in a ZIP Code). Therefore, in order to act against these high-calorie, nutrient-poor advertising messages [51], culturally tailored approaches are needed to promote healthful eating behaviors among this population [52]. In addition, health literacy has been identified as a key social determinant of health among adolescents [53].…”
Section: Future Directionsmentioning
confidence: 99%
“…The existing literature indicates that, on average, only one to two SCT concepts are employed in interventions to explain the childhood obesity-related behaviors. 19,21,22 Thus, the results of the study will assist public health professionals and others in more effectively using the SCT theory to design interventions targeting childhood obesity within rural, predominantly African American settings. Finally, this study promotes the importance of operationalizing, measuring, and applying the SCT concepts within the context of childhood obesity.…”
mentioning
confidence: 99%
“…20 In contrast, African American mother-child dyads experienced an increase in self-efficacy for diet and behavior changes (e.g., consumption of more fruit and vegetables in-and outside of the home and participation in more physical activity) after participation in an eHealth intervention. 21 Similarly, African American families discussed an increase in self-efficacy to start and sustain positive weight-related behaviors after participation in the Families Improving Together randomized controlled trial. 22 Other empirical studies have found relationships between self-efficacy and behavioral capability and self-efficacy and outcome expectations.…”
mentioning
confidence: 99%